Rents, Actors, and the Expansion of Commodity Frontiers in the Gran Chaco. Issue 1 (2nd January 2018) - le Polain de Waroux, Yann; Baumann, Matthias; Gasparri, Nestor Ignacio; Gavier-Pizarro, Gregorio; Godar, Javier; Kuemmerle, Tobias; Müller, Robert; Vázquez, Fabricio; Volante, José Norberto; Meyfroidt, Patrick
Abstract : Theories of frontier expansion in the last four decades have been mostly shaped by studies of state-driven smallholder colonization. Modern-day agricultural frontiers, however, are increasingly driven by capitalized corporate agriculture operating with little direct government intervention. The expansion of contemporary frontiers has been explained by the existence of spatially heterogeneous "abnormal" rents, which can be caused by cheap land and labor, technological innovation, lack of regulations, and a variety of other incentives. Here, we argue that understanding the dynamics of these frontiers requires considering the differential ability of actors to capture such rents, which depends on their access to production factors and their information, preferences, and agency. We propose a new conceptual framework drawing on neoclassical economics and political economy, which we apply to the South American Gran Chaco, a hot spot of deforestation for soy and cattle production. We divide the region into a set of distinct frontiers based on satellite data, field interviews, and expert knowledge, to review the drivers and actors of agricultural expansion in these frontiers. We show that frontier expansion in the Chaco responded to the rents created by new agricultural technologies, infrastructure, and rising producer prices but that the frontier dynamics were strongly influenced by actors' abilities to capture or influence these rents. Our findings thus highlight that understanding contemporary commodity frontiers requires analyzing the novel ways by which the agency of particular groups of actors shapes land-use outcomes.